Answer:
![f^(-1)(x)=√(x)+2](https://img.qammunity.org/2022/formulas/mathematics/high-school/p48kd8bdgntah7exalc0kwxoynmzmu10wm.png)
Explanation:
Given function is,
f(x) = (x - 2)²
Step - 1
Rewrite the function in the form of a equation.
y = (x - 2)²
Step - 2
Interchange the variables 'x' and 'y',
x = (y - 2)²
Step - 3
Solve the equation for y,
x = (y - 2)²
y - 2 = √x
y = 2 + √x
Step - 4
Rewrite the equation in the form of a function,
![f^(-1)(x)=√(x)+2](https://img.qammunity.org/2022/formulas/mathematics/high-school/p48kd8bdgntah7exalc0kwxoynmzmu10wm.png)